EP.TH.375Inguinal hernia repair: A systematic analysis of online patient information using the modified Ensuring Quality Information for Patients tool. (28th October 2021) - Chien, Siobhan; Cunningham, Danielle; Khan, Khurram
Abstract: Aims: Online resources are a fundamental source of healthcare information due to the increasing popularity of the Internet, therefore ensuring accuracy and reliability of websites is crucial to improving patient education and enhancing patient outcomes. Inguinal hernia repair is the most commonly performed general surgical procedure worldwide. This study aims to analyse the quality of online patient information on inguinal hernia repair using the modified Ensuring Quality Information for Patents (EQIP) tool. Method: A systematic review of online information on inguinal hernia repair was conducted using 4 search terms: "inguinal hernia", "groin hernia", "inguinal hernia repair" and "inguinoscrotal hernia". The top 100 websites for each term identified using Google were assessed using the modified EQIP tool (score 0-36). Websites for the paediatric population or intended for medical professional use were excluded from analysis. Results: 142 websites were eligible for analysis. 52.8% of websites originated from the UK. The median EQIP score for all websites was 17/36 (IQR 14-21). The median EQIP scores for Content, Identification and Structure were 8/18, 2/8, and 8/12, respectively. Complications of inguinal hernia repair were included in 46.5% of websites, with 9.2% providing complication rates and 14.1% providing information on how complications are handled. Conclusions: This study highlights that the current quality of online patient information on inguinal hernia repair is poor, with minimal information available on complications, hindering patients' ability to make informed decisions regarding their healthcare. To improve patient education, there is an immediate need for improved quality online resources to meet international standards.